Frap Assay and Nitric Oxide Free Radical Scavenging Activity of Aerial Parts of Ethanolic Extract of Cordia Obliqua - S. Sivakrishnan (Journal of Global Pharma Technology, 2019)
Objective: Oxidative stress resulting from accumulation of reactive oxygen species has been associated with disease. Research study was undertaken to investigate and evaluate the in vitro antioxidant activities such as FRAP and Nitric oxide of ethanolic extract of cordia obliqua.Methods: The ethanolic extract of cordia obliqua was examined by Nitric oxide radical scavenging activity and Ferric Reducing Antioxidant Power Assay with reference standard ascorbate respectively through in vitro models.Results: Ethanolic extract of cordia obliqua showed significant free radical scavenging activity than that of standard.Conclusion: In vitro study indicates that these plant extracts is a significant source of natural antioxidant, which might be helpful in preventing the progress of various oxidative stresses.